In Vitro Biological Evaluation of Aprepitant Based 177Lu-Radioconjugates - Paweł K. Halik; Przemysław Koźmiński; Joanna Matalińska; Piotr F. J. Lipiński; Aleksandra Misicka; Ewa Gniazdowska (MDPI AG, 2022)
Currently, the search for promising NK1R-positive tumor-targeting radiopharmaceuticals based on the structure of small molecular antagonists of neurokinin-1 receptor can be observed. Following this trend, we continued our evaluation of aprepitant-based 177Lu-radioconjugates in terms of future oncological applications. For this purpose, three novel aprepitant homologues were synthesized to broaden the previously obtained derivative portfolio, functionalized with the DOTA chelator and labeled with 68Ga and 177Lu. The newly evaluated radioconjugates showed the intended significant increase in lipophilicity compared to the previous ones, while maintaining stability in the human serum. Then, in a receptor binding study to the human NK1 receptor, we compared the two series of 177Lu-radioconjugates of aprepitant with each other and with the reference Substance P derivative currently used in glioblastoma therapy, clearly indicating the high affinity and better binding capacity of the novel radioconjugates. The in vitro experimental results included in the presented study, supported by labeling optimization, radioconjugate characterization and docking modeling of new aprepitant-derived radioagents, confirm our assumptions about the usefulness of aprepitant as a NK1R targeting vector and point out the perspectives for the forthcoming first in vivo trials.